Characterization and Evaluation of Antimicrobial Activity of Sorbitan Isolated from the Leaves of Securidaca longipedunculata (Fresen) (retracted) (CaJoST, 2024)
Securidaca longipedunculata is a shrub of the family Polygalaceae. It is apotent medicinal plant used in management of microbial infection others.The aim of this study is to characterize, and evaluate the antimicrobialactivity of sorbitan isolated from the leaves of Securidaca Longipedunculata(Fresen). The methanol extract of S. longipedunculata was subjected tochromatographic purification, which led to isolation of compound identifiedas sorbitan by analysis of the 1D and 2D-NMR spectral data. Theantimicrobial screening against bacterial pathogens (Methicillin-resistantstaphylococcus aureus (MRSA), Vancomycin-resistant enterococci (VRE) S.aureus, S. feacalis, E. coli, S. typhimurium, P. fluorescens, K. pneumoniea)and fungal pathogens (C. albicans, C. krusei, A. niger, A. fumigates, andMicrosporumcanis) was performed using agar well diffusion and brothdilution method. In-vitro inhibition of these pathogenic microorganismsproduced inhibition zone ranging from 25 - 32 mm for sorbitan; the standarddrugs sparfloxacin and ciprofloxacin (500µg/mL) had zone of inhibitionranging from 28 - 40 mm. While the antifungal drugs fluconazole and Fulcinexhibited zone of inhibition ranging from 27 mm to 34 mm. Minimuminhibition concentration (MIC) values of sorbitan ranged from 25 - 12.5mg/mL. The minimum bactericidal concentration (MBC)/minimum fungicidalconcentration (MFC) of sorbitan was observed to be 50 - 25 mg/mL.Sorbitan was isolated and characterized from S. longipedunculata leavesextract and it demonstrated good antimicrobial activity which validates theused of the plant leaves in the treatment of microbial infections in traditionalmedicine